Bioinformatics Algorithms - C. Kuppuswamy (Dominant Publishers, 2007)
This book on Bioinformatics Algorthms has been dsigned to focus on descrete algorithms that address important problems in molecular biology, genomics, and genetics, that are based on sound models which are computationally efficient, that have been implemented and tested, in simulations and on real databsets, providing new biological results. Thus introductory text of the book offers a clear exposition of the algorithmic principels driving advances in bioinformatics.